How do Latina patients experience integrated care? - Rivera, Veronica, author; Davies, Timothy G., advisor; Anderson, Sharon, committee member; Haddock, Shelley, committee member; Aragon, Antonette, committee member (Colorado State University. Libraries, 2017)
The underutilization of mental health services by Latinos and Latinas in the US is often attributed to factors such as cultural beliefs and perceptions about mental health; lack of awareness of the available services; and socio-economic matters. In order to improve the access to mental health services for Latinos, it is necessary to learn about their experience of these services. The purpose of this study was to gain understanding of patients from Latin-America making meaning of their experience as recipients of mental health services at two community health clinics that offer integrated care services. This is a phenomenological study that aims to understand the factors influencing Latina patients' decision about whether or not to follow up on subsequent mental health care appointments. Eighteen Latina women who had attended mental/ behavioral health services at the family health clinic were interviewed about their experiences. The first main theme to arise was patients' symptoms and the referral process. This included services requested by the patient or offered by the clinic, trust in the referring personnel, and familiarity with mental health services. The second theme was the behavioral health specialist's attitude and clinical approach, including personal qualities, clinical skills and knowledge. The third theme was the outcomes; these included improvement of symptoms and behavior, improved level of functioning, and better understanding of the situation. The essence of the findings was the overall feeling about their experience at the clinic, and the benefit to see the psychotherapist in the same health clinic in which they received medical services. Keywords: Primary care, integrated care, Latino mental health, behavioral health, cultural competency, behavioral health consultant.
Keywords: behavioral health consultant; integrated care; primary care; cultural competency; behavioral health; Latino mental health